Ukrain, a plant derived semi-synthetic compound, exerts antitumor effects against murine and human breast cancer and induce protective antitumor immunity in mice - Bozeman, E.N.; Srivatsan, S.; Mohammadi, H.; Daniels, D.; Shashidharamurthy, R.; Selvaraj, P. (Experimental Oncology, 2012)
Despite the recent advances in anti-cancer therapies, breast cancer accounts for the highest percentage of estimated new cases among female cancer patients. The anti-cancer drug Ukrain, a plant-derived semi-synthetic compound, has been shown to be effective in a variety of tumor models including colon, brain, ovarian, melanoma and lymphoma. However, the direct cytotoxic effects of Ukrain have yet to be investigated in breast cancer models. Aim: Herein, we investigated the in vitro and in vivo cytotoxicity of Ukrain using murine (4T07 and TUBO) and human (SKBR-3) breast cancer cell lines. Methods: Cells were treated with varying concentrations of Ukrain for up to 72 h and analyzed for viability by trypan blue exclusion, apoptosis by intracellular caspase 3 and Annexin V staining, and proliferative potential by a clonogenic assay. Female BALB/c mice were challenged subcutaneously (s.c.) with 4T07-RG cells and administered 5 mg/kg or 12.5 mg/kg body weight Ukrain intravenously (i.v.) on the same day and 3 days later. Protective immune responses were determined following re-challenge of tumor-free mice 35 days post primary challenge. Results: Ukrain exposure induced apoptosis in a dose and time-dependent manner with 50 µg/mL Ukrain leading to >50% cell death after 48 h exposure for all three breast cancer cell lines. Ukrain administration (12.5 mg/kg) led to significant inhibition of 4T07 tumor growth in vivo and sustained protective anti-tumor immunity following secondary challenge. Conclusion: Our findings demonstrate the in vitro and in vivo cytotoxic effects of Ukrain on breast cancer cells and may provide insight into designing Ukrain-based therapies for breast cancer patients.